Crosstalk between Virulence Loci: Regulation of Salmonella enterica Pathogenicity Island 1 (SPI-1) by Products of the std Fimbrial Operon - López-Garrido, Javier; Casadesús, Josep (PLOS ONE, 2012)
Invasion of intestinal epithelial cells is a critical step in Salmonella infection and requires the expression of genes located in Salmonella pathogenicity island 1 (SPI-1). A key factor for SPI-1 expression is DNA adenine (Dam) methylation, which activates synthesis of the SPI-1 transcriptional activator HilD. Dam-dependent regulation of hilD is postranscriptional (and therefore indirect), indicating the involvement of unknown cell functions under Dam methylation control. A genetic screen has identified the std fimbrial operon as the missing link between Dam methylation and SPI-1. We show that all genes in the std operon are part of a single transcriptional unit, and describe three previously uncharacterized ORFs (renamed stdD, stdE, and stdF). We present evidence that two such loci (stdE and stdF) are involved in Dam-dependent control of Salmonella SPI-1: in a Dam− background, deletion of stdE or stdF suppresses SPI-1 repression; in a Dam+ background, constitutive expression of StdE and/or StdF represses SPI-1. Repression of SPI-1 by products of std operon explains the invasion defect of Salmonella Dam− mutants, which constitutively express the std operon. Dam-dependent repression of std in the ileum may be required to permit invasion, as indicated by two observations: constitutive expression of StdE and StdF reduces invasion of epithelial cells in vitro (1,000 fold) and attenuates Salmonella virulence in the mouse model (>60 fold). In turn, crosstalk between std and SPI-1 may play a role in intestinal infections by preventing expression of SPI-1 in the caecum, an intestinal compartment in which the std operon is known to be expressed.